Prediction Model of Health-Related Quality of Life in Adolescents with Early Marriage Decisions in Bandar Lampung - Abdullah Azzam Suyuthi; Suharmanto Suharmanto; Khairun Nisa Berawi; Jhons Fatriyadi Suwandi; Sutarto Sutarto (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Early marriage in Lampung exhibited a rate above national average, reaching 7,11%. Early marriage would impact significantly for adolescents because their quality of life in physical, mental health and social functioning aspect was decreasing. This study aimed to analyze the differences in average quality of life scores and develop a predictive model for health-related quality of life among adolescents who decided to marry early in Bandar Lampung. This research utilized a quantitative analytical observational method with a cross-sectional approach. The population and sampling technique involved 116 individuals (both males and females) who entered their first early marriage during 2021-2025 period. Data were analyzed using Anova, T Test and multiple linear regression. The results of the bivariate analysis showed that only two variables were significantly associated with the quality of life of adolescents who married early (p<0,05): parenting style (p=0,019) and family support (p=0,045). The results of multivariate analysis obtained an R2 value of 10.6%, which meant that the research variables affected quality of life by 10.6%. In the multiple linear regression model, the model formula obtained was Y (Quality of Life) = 44,469 -3,036 (Parenting pattern) - 3.497 (Social support). This meant that one-unit increase in the parenting pattern variable, with social support considered constant, would decrease the quality of life of adolescents by 3.036 units. These findings indicate that social support and parenting variables act as factors that encourage a decline in the quality of life of adolescents, not as protective factors that protect their quality of life.